(untitled) (Andamios, Revista de Investigación Social, 2013)
There is not a evaluation`s methodology for analysis public policy agreed and widely accepted. This article propose, with the strict scientific rigor required, a methodological framework that can guide the analytical work of critical and constructive evaluation of the public interventions. So, it provides some useful theoretical insights from the epistemological framework to determine the principles, approach and method, as well as the choice of techniques and analytical tools that have to be part of, in practice, the mainstay of the evaluation processes of public policy.